The role of physical activity and sport in children and adolescents with autism spectrum disorder (ASD) <subtitle>A narrative review</subtitle> - Agata Małgorzata Zborowska (Hogrefe AG, 2024)
Abstract: Background: Various health-related benefits of physical activity (PA) in children and adolescents have been reported, with suggestions that PA could effectively address certain deficits found in autism spectrum disorder (ASD). However, there remains insufficient engagement in PA among individuals with ASD, and barriers to accessing PA persist. Objective: This study aims to review PA interventions (types, frequencies, and durations) in ASD over the last five years and discuss their effects. Methods: Searches were conducted in the PubMed database from October to December 2022 using Mesh Terms: "adolescent" OR "children" AND "sport" OR "physical activity" AND "mental health" AND/OR "autism." Results were critically appraised using PEDro and Cochrane's ROB-2, categorized into five stages to assess potential bias. Results: A total of ten papers were included and appraised, examining various types of PA. Primary benefits observed in children and adolescents included the development of social skills, reduction of autistic traits, regulation of emotions, and management of behaviour and cognition. Conclusions: Evidence indicates that PA can effectively address some neuropsychological deficits in ASD. Additionally, managing and protecting against metabolic conditions through PA can significantly enhance overall health.